The (Social) Media is the Message: Theories of Liability for New Media Artists - Kelly, Beatrice (The Columbia Journal of Law & the Arts, 2017)
Artists have always challenged the limits of the legal, but in recent years, there has been a shift from works of art that offend or upset to those that merely run afoul of something very mundane: online terms of service. This Note argues that new media artists working primarily with social media must be aware of the potential liability inherent in any project that involves a violation of user agreements. If artists continue to violate the user agreements of social media websites—whether purposefully or by accident—there are serious implications for legal liability. With Richard Prince standing at the helm of a new breed of artist-plaintiff, the new media movement is beginning to witness the very tangible presence of litigation in even the most intangible of artworks.